Entre la geografía y la arqueología: el espacio como objeto y representación - Villafañez, Emilio Alejandro (Revista de Geografía Norte Grande, 2011)
Geography, the science of the spatial, and archeology, responsible for studying people through their material remains, have shared in the course of their history much more than is commonly assumed. The need to study social groups and their relationship to space is today, one of the keys to understanding the dynamics of these groups (both current and past). If space is a mere "backdrop" or a social construct, is something that at first was a problem only in geography, but which also influenced other sciences, as in the case of archeology. In this article, we provide a general panorama, analyzing existing bibliographic material, to review theoretical and methodological postures about what the spatial have meant to linking these disciplines.